Energy consumption and economic growth nexus: New evidence from Pakistan using asymmetric analysis. (15th December 2019) - Baz, Khan; Xu, Deyi; Ampofo, Gideon Minua Kwaku; Ali, Imad; Khan, Imran; Cheng, Jinhua; Ali, Hashmat
Abstract: This study contributes to the extant literature on the nexus among energy consumption, agriculture, capital and economic growth in Pakistan. We use time series data from 1971 to 2014 and employ the Non-linear Autoregressive Distributed Lag (NARDL) model. The NARDL testing results affirms asymmetric co-integration among the variables. Asymmetric causality is noted between positive shocks in energy consumption and economic growth running from energy consumption to economic growth. A feedback effect is found between agriculture and economic growth for positive shocks. A unidirectional nexus is noted between capital and economic growth for both positive and negative shocks. Similarly, the results of a Granger causality test indicate symmetric causality between energy consumption, agriculture, capital and economic growth. This research suggests that policymakers should revisit their policies regarding agriculture and energy sectors by attracting foreigner investors to build new hydropower dams to both affirm the availability of energy to the industrial sector and control the scarcity of water. Highlights: Nonlinear nexus examine among energy, agriculture, capital, and economic growth . Asymmetric nexus observed for Pakistan over the span of 1971–2014. We examined asymmetric co-integration among the variables. Asymmetric growth nexus noted between energy consumption and economic growth.